2016
DOI: 10.1590/1414-462x201600030142
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in fish and sediment of Purus River, Acre State, Amazon

Abstract: Core subject To quantify the Hg content of sediment and fish collected along the Purus River (Acre State, Amazon) in order to identify if those samples could be a potential route of Hg exposure to the population of Manoel Urbano (a riverside community). Methods The total mercury (THg) was quantified using the Cold Vapor Atomic Absorption technique. Results We collected 06 samples of sediment and 264 samples of fish. The Hg in sediments ranged between 0.038 and 0.065 µg.g–1.The results indicate that sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
3
Order By: Relevance
“…454/2012 for sediments, in which Hg values below 170 ng g −1 present a low probability of adverse effects on biota and Hg concentrations above 486 ng g −1 would cause effects on organisms exposed to Hg. However, Castro et al (2016) found low concentrations of Hg in sediments but detected higher concentrations in the muscles of carnivorous fish.…”
Section: Resultsmentioning
confidence: 89%
“…454/2012 for sediments, in which Hg values below 170 ng g −1 present a low probability of adverse effects on biota and Hg concentrations above 486 ng g −1 would cause effects on organisms exposed to Hg. However, Castro et al (2016) found low concentrations of Hg in sediments but detected higher concentrations in the muscles of carnivorous fish.…”
Section: Resultsmentioning
confidence: 89%
“…In this context, it is important to emphasize the need for further studies to quantify the risks to aquatic biota and human health in the Pelotas River basin. Castro et al, 2016 *This study; Impact: human activities conducted in the drainage basins correlated to the increase of Hg concentration in the sediments of their respective rivers, as cited by the authors. M: gold mining; GO: organomercurial fungicides; A: Agriculture; I: Industrial production of chloride and soda; NR: non-reported group.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the concentrations found in the Pelotas River show a low probability of risk to the biota. Nevertheless, Castro et al, (2016) demonstrated the bioaccumulation potential of Hg when studying the Purus River. These researchers found Hg concentrations between 38 and 65 ng g -1 in the sediment of the Purus River, while in carnivorous fish muscle, it reached up to 5384 ng g -1 , with an average of 927 ng g -1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to World Health Organization (WHO, 2006), recommended safety limit for fish consumption is 0.5 mg/kg of mercury. However, in Brazilian Amazon, studies have shown several fish species (carnivores, omnivores, planktivores, and piscivores) above this threshold limit (Kasper et al, 2012;Bastos et al, 2015;Castro et al, 2016;Lino et al, 2018). In Manuel Hydroelectric reservoir on Jamari River, carnivorous fish species presented high levels of mercury concentration upstream (0.545 mg/kg) and downstream of reservoir (1.366 mg/ kg; Kasper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%